Prostate Cancer Screening Disparities in Persons Experiencing Homelessness. Issue 11 (7th November 2022) - Mayo, Zachary S.; Kilic, Sarah S.; Weleff, Jeremy; Parker, Sean M.; Strzalka, Colleen; Phelan, Michael; Mian, Omar Y.; Stephans, Kevin L.; Suh, John H.; Tendulkar, Rahul D.
Abstract : PURPOSE: The purpose of this study was to assess prostate-specific antigen (PSA) testing rates in persons experiencing homelessness (PEH), identify factors associated with screening, and compare PSA screening rates in PEH with a matched cohort of persons not experiencing homelessness (non-PEH). MATERIALS AND METHODS: We identified 9, 249 potentially eligible PEH cared for at a large metropolitan hospital system from an institutional registry of all patients who presented to the health care system as homeless from 2014 to 2021. Homelessness was defined by the presence of the Z-code for homelessness (Z59), the listed address matching to the address of a homeless shelter or other transitional housing or a positive screen for homelessness. A matched cohort of 10, 000 non-PEH was generated for comparison. Univariate chi-square analysis and multivariate logistic regression were performed to evaluate variables associated with PSA testing. RESULTS: A total of 1, 605 PEH and 3, 413 non-PEH were eligible for PSA screening within the study timeframe. Half of PEH were Black (50%). Medicaid was the most common insurance (51%), followed by Medicare (18%). PEH were less likely to have a PCP (58% v 81%, P < .001) and had a significantly lower PSA testing rate (13% v 34%, P < .001) compared with non-PEH. Univariate analysis revealed that PSA testing was more common in PEH who were employed ( P < .001), had private insurance or Medicare ( P < .001), or had an established primary care provider (PCP; P < .001). Multivariate analysis confirmed that having a PCP (OR, 2.54; 95% CI, 1.62 to 4.00; P < .001) significantly increased the likelihood of PSA testing in PEH. CONCLUSION: PEH experience low rates of prostate cancer screening. Interventions to increase screening in this population, including increased PCP access, are needed.